Infliximab decreases inflammatory activity but has no effect on small fiber neuropathy related symptoms in Dutch patients with sarcoidosis - Raasing, Lisette; Vogels, Oscar J.M.; Veltkamp, Marcel; Grutters, Jan C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background and aim: Small fiber neuropathy (SFN) may present as complication in sarcoidosis.(1) SFN can potentially result into a large range of symptoms with a high impact on quality of life.(2) Although treatment of the underlying disease of SFN is paramount, little research has been performed to investigate SFN improvement as consequence of sarcoidosis treatment. This retrospective study investigates whether there is an association between the anti-inflammatory effects of infliximab and SFN-symptoms Methods: The Small Fiber Neuropathy Screening List (SFNSL) was used to measure changes in SFN symptoms during infliximab treatment. Maximal standardized uptake value (SUVmax) from Fluordeoxyglucose Positron Emission Tomography (FDG-PET) was used as a measure for inflammatory activity. Results: 36 sarcoidosis patients were eligible for analysis. SFNSL-score showed a mean decrease of -1,9 points (p = 0.446). SUVmax did improve with a mean of -3.7 (p<0.001). No correlation between a decrease of SUVmax and SFNSL screening list could be found (p=0.610). Conclusions: Our data reveal no association between anti-inflammatory effect of infliximab and SFN-related symptoms in patients with sarcoidosis, which contradicts previous case-reports and case-series.(3–6) Given the major negative impact of SFN-related symptoms on the quality of life in patients with sarcoidosis, it is necessary that the possible beneficial effect of anti-inflammatory therapy will be further addressed in future prospective studies.1